Debugging Distributed Systems. - BESCHASTNIKH, IVAN; WANG, PATTY; BRUN, YURIY; ERNST, MICHAEL D. (Communications of the ACM, 2016)
The article discusses particular issues with debugging distributed systems, noting tools and research related to distributed systems. Topics include the visualization of distributed-system executions, the role of keyword search and structured search in debugging, and the use of the tool ShiViz in debugging distributed systems.